Mudskipper β-def2 exhibits potent broad-spectrum bactericidal activity via membrane-disrupting and DNA-targeting mechanisms - Hu, Ya-Zhen; Tan, Ning-Xi; Cao, Jia-Feng; Chen, Jiong (Fish & shellfish immunology, 2025)
Defensins, cysteine-rich host defense peptides critical for host's antibacterial immunity, remain understudied in intertidal living species. Here, we characterize muβ-def2, a 43-amino-acid β-defensin from mudskipper with three pairs of disulfide structures (C1-C5, C2-C4, C3-C6) and a cationic amphiphilic topology, featuring a hydrophobic face and a charge-rich surface (+4.5 net charge, pI 8.9). Phylogenetic analysis reveals its tight clustering within the β-def2 subclass, highlighting conserved evolutionary antimicrobial functions. muβ-def2 exhibits potent broad-spectrum bactericidal activity, with minimum bactericidal concentrations (MBCs) ranging from <1 μM (e.g., S. aureus) to 32 μM (L. monocytogenes), and rapid killing kinetics (e.g., A. veronii eradication within 160 min). This activity persists across temperature (28°C-100 °C) and pH (5.5–9.0) extremes, underscoring environmental robustness. Mechanistically, muβ-def2 disrupts bacterial membranes through selective targeting of prokaryotic phospholipid surfaces, with subsequent detection of genomic DNA interactions that likely occur as a downstream consequence of membrane permeabilization. Notably, incubation with pathogen-associated molecular patterns (PAMPs) diminishes its bactericidal efficacy, suggesting competitive inhibition of peptide-PAMP interactions. These findings elucidate a dual membrane-DNA attack mechanism for muβ-def2, emphasizing its potential as an antimicrobial agent that may also be used for therapeutic applications against multidrug-resistant pathogens. •muβ-def2 has broad-spectrum and stable bactericidal activity.•muβ-def2 kills bacteria via membrane disruption and subsequent genomic DNA interactions.•Competitive binding interactions between PAMPs and muβ-def2 significantly attenuate the peptide's bactericidal efficacy.